Metabolismo de Flavonoides por Spodoptera frugiperda e Anticarsia gemmatalis - Negra, Bruno Luis Della (2019)
The soybean plant (Glycine max L. Merryl) produces a range of flavonoids as secondary metabolites, known to cause damage to herbivorous insects. However, Spodoptera frugiperda and Anticarsia gemmatalis (Lepidoptera: Noctuidae) can feed on soybean leaves, causing great losses in Brazilian crops. Surprisingly, little is known about how these insects metabolize soybean flavonoids, and how their metabolism explains their status as agricultural pests. Therefore, the present work aims to evaluate the toxicity of model flavonoids quercetin and rutin in the development of S. frugiperda and A. gemmatalis, in addition to elucidate the metabolic strategies used by these insects to deal with flavonoid toxicity. The insects were reared in artificial diets containing quercetin and rutin. Larval weights, larval stage durations, and mortality were followed during the experiments. Feces samples from caterpillars were analyzed by LC-MS to identify metabolites from quercetin and rutin, as well as naringenin. In vitro enzymatic assays with insect midgut tissue using quercetin and rutin together with UDP-glucose were performed in order to confirm the production of glucosylated metabolites found in feces. Quercetin and rutin showed toxicity in the diet, resulting in lower larval weights and longer larval stages for both insect species. Glucosylated, methylated, and sulfonated derivatives were detected in feces extracts, as well as di- and tri-glucosides and combinations of these functionalizations, including different regioisomers. S. frugiperda also produced phosphorylated metabolites of quercetin and naringenin. Both species are able to metabolize quercetin, rutin and naringenin, generating potentially less toxic compounds. Some glycosides were also observed in enzymatic assays, confirming the activity of UDP-glucosyltransferases in flavonoid metabolism. The experiments presented here provide qualitative data about the biochemical reactions employed by S. frugiperda and A. gemmatalis in flavonoid metabolism and contribute to future studies on their interactions with chemically defended host-plants.